2012
DOI: 10.1210/jc.2011-3010
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nonalcoholic Fatty Liver Disease (NAFLD) and Osteoporotic Fracture in Middle-Aged and Elderly Chinese

Abstract: The presence of NAFLD was significantly associated with a recent history of osteoporotic fracture in middle-aged and elderly Chinese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 32 publications
8
123
1
2
Order By: Relevance
“…Moon and colleagues observed reduced BMD of the lumbar spine in postmenopausal patients with NAFLD, regardless of the presence of MS, and after taking into account other risk factors for low BMD (body mass index, age, and smoking) [Moon et al 2012]. Decreased BMD in NAFLD appears to be independent of sex, which is consistent with the results of a retrospective study involving more than 7000 men, in which the presence of NAFLD was associated with a 2.5-fold increased risk of osteoporotic fractures [Li et al 2012]. Purnak and colleagues did not observe a relationship between simple steatosis and BMD [Purnak et al 2012].…”
Section: Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepasupporting
confidence: 84%
“…Moon and colleagues observed reduced BMD of the lumbar spine in postmenopausal patients with NAFLD, regardless of the presence of MS, and after taking into account other risk factors for low BMD (body mass index, age, and smoking) [Moon et al 2012]. Decreased BMD in NAFLD appears to be independent of sex, which is consistent with the results of a retrospective study involving more than 7000 men, in which the presence of NAFLD was associated with a 2.5-fold increased risk of osteoporotic fractures [Li et al 2012]. Purnak and colleagues did not observe a relationship between simple steatosis and BMD [Purnak et al 2012].…”
Section: Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepasupporting
confidence: 84%
“…Patients with NAFLD have been reported to have decreased BMD [34,35] and increased risk of fractures [36], although not all studies concur [37,38]. In our population we found no difference in BMD or bone turnover markers between NAFLD patients and controls; however, sclerostin levels were positively correlated with BMD in our patients, in accordance with previous studies in different populations; we previously reported, for the first time, a positive correlation between sclerostin and BMD in postmenopausal osteoporosis [39], a finding validated by other authors in distinct metabolic bone diseases [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent cross-sectional and case-control studies involving both adults and children or adolescents have consistently demonstrated that the prevalence of decreased BMD (as measured by dual-energy X-ray absorptiometry) is significantly increased in patients with NAFLD (Table 1) [9][10][11][12][13][14][15][16][17].…”
Section: Epidemiological Evidence Linking Nafld With Low Bmdmentioning
confidence: 99%